ALGORITHM FOR EARLY DIAGNOSIS OF POST-INFECTIOUS MYOCARDITIS IN INFANTS FOLLOWING ACUTE RESPIRATORY INFECTIONS (Modern American Journal of Medical and Health Sciences, 2026)
Acute respiratory infections (ARI) are among the most common diseases in infants and may lead to various complications affecting different organ systems, including the cardiovascular system. One of the most serious complications is myocarditis, which represents an inflammatory process of the heart muscle and can lead to severe functional disturbances of cardiac activity. Early diagnosis of post-infectious myocarditis in infants remains a challenging clinical problem due to the nonspecific nature of symptoms and the physiological characteristics of early childhood. Delayed identification of myocardial inflammation may increase the risk of heart failure, arrhythmias, and long-term cardiovascular complications.The aim of this study is to develop an algorithm for the early diagnosis of myocarditis in infants following acute respiratory infections and to analyze the clinical and diagnostic features associated with this condition. The research focuses on identifying key clinical symptoms, laboratory indicators, and instrumental diagnostic findings that may assist in the early detection of myocardial involvement after respiratory infections.